Costituzionalizzare la Costituzione Una prospettiva pleromatica - FRANZA, Teresa (Premio Ricerca «Città di Firenze», 2017)
In a context that may seem, to a fairly realistic pessimist, of forced choice between fanatic neo-fundamentalisms and trivializing single thought, a 'common cause' like the Italian Constitution offers itself as a reference to which to look at with motivated trust from different perspectives and situations, often conflicting. To constitutionalize means to make the Constitution more authentically itself by preserving what is to be guarded and creating what is yet to be created. The underlying theme and highly original contribution of this book is the concept of pléroma or fullness of being: a strategic concept that enhances the original personalism of the Constitution and absorbs - by unifying and orienting - the restoring, interpreting and integrating of the constitutional text, proposing a political-legal project in line with the current times.